Minimally invasive closure of a progressive pseudoaneurysm of the ascending aorta: A case report - Wu, Yuan; Fan, Linglin; Liu, Fei; Zhuang, Hui; Wu, Xijie (Frontiers in Cardiovascular Medicine, 2023)
Ascending aortic pseudoaneurysm (AAP) is rare but may cause life-threatening complications. Although the placement of a stent graft and the use of occluder devices and vascular plugs to exclude pseudoaneurysm are adopted for some patients, the management of progressive pseudoaneurysms that may rupture at any time remains a challenge that needs to be addressed. In this study, we present the case of a patient with an AAP that was caused by aortic and mitral valve replacement for the giant left ventricle. Aortic pseudoaneurysm was suspected on the basis of a spherical cystic echo (70 × 80 mm) of the ascending aorta; this pseudoaneurysm was detected by an ultrasonic cardiogram, and the diagnosis was confirmed by an aortic computed tomography angiography (CTA) examination. To prevent the unexpected rupture of a progressive pseudoaneurysm, our patient was treated with a 28- mm ASD occluder without any procedural complications. Our patient has a good prognosis, which will inspire clinicians to choose minimally invasive procedures when dealing with such high-risk cases in emergency situations.